The immune system as a system of relations - Daëron, Marc (Frontiers in Immunology, 2022)
Progress in neuroimmunology established that the nervous and the immune systems are two functionally related physiological systems. Unique sensory and immune receptors enable them to control interactions of the organism with the inner and the outer worlds. Both systems undergo an experience-driven selection process during their ontogeny. They share the same mediators/neurotransmitters and use synapses for intercellular communication. They keep a memory of previous experiences. Immune cells can affect nervous cells, nervous cells can affect immune cells, and they regulate each other. I however argue that the two systems differ by three major points: 1) Unlike the nervous system, the immune system has a loose anatomical structure, in which molecular and cellular events mostly occur at random; 2) The immune system can respond to molecules of the living world whereas the nervous system can respond to phenomena of the physical world; 3) Responses of the immune system act both on the organism and on the stimulus that triggered the response, whereas responses of the nervous system act on the organism only. The nervous and the immune systems therefore appear as two complementary systems of relations that closely work together, and whose reactivities are well-suited to deal with physical and biological stimuli, respectively. Its ability both to adapt the organism to the living world and to adapt the living world to the organism endows the immune system with powerful adaptive properties that enable the organism to live in peace with itself and with other living beings, whether pathogens or commensals.